Analysis of compression ignition engine characteristics with addition of MTBE with diesel. (2021) - Godwin Antony, A.; Rajaguru, K.; Dinesh, S.; Radhakrishnan, K.; Parameswaran, P.; Saravanan, K.
Abstract: Incomplete combustion in IC engines reduces the efficacy and increases the release of undesired contents to the atmosphere. As an effort to improve the properties of emission and the performance characteristics of the engine, additive MTBE is added to gasoline at different proportions. This work aims at comparison of efficacy and emission characteristics of the plain and MTBE blended gasoline fuel. MTBE was added to the neat fuel in proportions of 5, 10 and 15 ml per 100 ml of gasoline. An upward trend was observed with the BSFC and BTE for blended fuel when compared to the neat fuel. Also, the characteristic of emission of the blended fuel was evaluated with the neat fuel and was observed with downfall in emissions of HC and CO. The emission of CO2 and oxides of nitrogen showed an upward trend with increase in blending ratio.